2011
DOI: 10.1007/s00259-011-1992-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of synthetic anti-HER2 Affibody molecules site-specifically labelled with 111In using N-terminal DOTA, NOTA and NODAGA chelators in mice bearing prostate cancer xenografts

Abstract: Since distant prostate cancer metastases are situated in bone or bone marrow, the higher tumour-to-bone ratio is the most important. This renders (111)In-DOTA-Z(HER2:S1) a preferable agent for imaging of HER2 expression in disseminated prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
63
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(72 citation statements)
references
References 39 publications
9
63
0
Order By: Relevance
“…High contrast results largely from high affinity of radiotracers and rapid pharmacokinetics. By comparison with other molecular imaging probes, Affibodies benefit from a short blood circulation time and high target affinity resulting in high-contrast images within a relatively short time after injection, and slower internalization rates (26,34,35). This permits utilization of more widely available short-lived radioisotopes, such as 18 F and 68 Ga, minimizing the patient's dosimetry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High contrast results largely from high affinity of radiotracers and rapid pharmacokinetics. By comparison with other molecular imaging probes, Affibodies benefit from a short blood circulation time and high target affinity resulting in high-contrast images within a relatively short time after injection, and slower internalization rates (26,34,35). This permits utilization of more widely available short-lived radioisotopes, such as 18 F and 68 Ga, minimizing the patient's dosimetry.…”
Section: Discussionmentioning
confidence: 99%
“…In this context previous Affibodies labeled with 68 Ga or 111 In showed approximately 10-fold higher renal localization than that seen in tumor (34,35,38), precluding imaging of tumors in the region around the kidney, as well as having an impact on dosimetry. Bioconjugation of the Affibody molecule with albumin, histidine containing tags or 18 F radiolabels have been proposed as alternative approaches to avoid tubular reabsorption and permitting rapid glomerular filtration (26,(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…In principle, uptake in these organs might be specific. However, a numerous studies with parental Z HER2:343 and its derivatives having the same binding site have demonstrated that uptake in these organs is not saturable, and therefore nonspecific [40][41][42][43][44]. Much lower uptake was also for radiolabeled PEP09239 having the same binding site and higher affinity to HER2.…”
Section: Vivomentioning
confidence: 99%
“…Elevated uptake of radiopeptides in these organs is usually associated with higher hydrophobicity. Indeed, evaluation using two scales of amino acid hydrophobicity [45,44] suggests that Z HER2:342min is slightly more hydrophobic than PEP09239. Our previous studies on 3-helix Affibody molecules suggest that such minor difference might be enough to cause noticeable increase of hepatic uptake and/or hepatobiliary excretion [47].…”
Section: Vivomentioning
confidence: 99%
“…These conjugates include affitoxin [101], pseudomonas exotoxin [102,103], ricin A chain [104], various probes (radioactive and nonradioactive) [104][105][106][107][108][109][110][111][112], photosensitizers [113][114][115], RNAse [116,117], cytokines [118] or chemotherapeutic agents [119][120][121][122]. A Phase II study of a novel future science group HER2/neu: an increasingly important therapeutic target.…”
Section: Pertuzumabmentioning
confidence: 99%